(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
Social-emotional education has become a determining factor in the development of young people and has not been taken into account in a crucial way in current learning strategies. We seek, by means of an investigative method of diverse documents of different authors, to give a conceptualization of the importance of socioemotional education in early childhood, as well as to introduce teachers to the idea that socioemotional education has a vital role in the work of the individual as a social and complete being. As a consequence, two points of utmost importance can be identified, one being the introduction of the socioemotional concept and its high influence on personal development in different contexts such as the academic and social ones, on the other hand, various pedagogical strategies are presented that have behind them the work of working on the socioemotional aspect in early childhood, thus helping teachers to expand their methodology by incorporating a series of guidelines that will be of great help.